1999
DOI: 10.1051/rnd:19990508
|View full text |Cite
|
Sign up to set email alerts
|

Sperm production, testicular size, serum gonadotropins and testosterone levels in Merino and Corriedale breeds

Abstract: -The relationships between testis size, hormone secretion and sperm production were studied during the spring (December) and autumn (May)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…There are differences in opinion about the relationship between testicular measurements and spermatological characteristics in rams. While several researchers concluded that there are favourable genetic and phenotypic correlations between semen characteristics and testicular measurements in rams (Rege et al, 2000) others reported no relationship between testicular size and sperm production measured at the same time (Fernandez-Abella et al, 1999). In the present study a significant positive correlations were observed between all testicular measurements with semen volume and motility rate at seven and eight months of age, while no correlation was found from nine to 14 months of age (Table 3).…”
Section: Resultssupporting
confidence: 43%
See 1 more Smart Citation
“…There are differences in opinion about the relationship between testicular measurements and spermatological characteristics in rams. While several researchers concluded that there are favourable genetic and phenotypic correlations between semen characteristics and testicular measurements in rams (Rege et al, 2000) others reported no relationship between testicular size and sperm production measured at the same time (Fernandez-Abella et al, 1999). In the present study a significant positive correlations were observed between all testicular measurements with semen volume and motility rate at seven and eight months of age, while no correlation was found from nine to 14 months of age (Table 3).…”
Section: Resultssupporting
confidence: 43%
“…While some researchers suggested that testicular size provided a good index of testicular sperm output in rams (Lino, 1972), others reported that biweekly scrotal measurements were poorly correlated with semen quality in adult rams (Langford et al, 1989). Fernandez et al (1999) did not record a relationship between testicular size and sperm production. In contrast, testicular volume during late spring was correlated with sperm production in autumn.…”
Section: Introductionmentioning
confidence: 97%
“…However, Fernandez‐Abella et al. () in Uruguay observed that there was no relationship between testicular size determined by orchimetry and sperm production measured at different times of the year in rams varying in the duration of the breeding season (Corriedale and Merino genotypes). In a previous study of sexually mature Santa Iněs rams, scrotal circumference was positively correlated only with sperm motility (Batissaco et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, Edens and Sefton [6] reported that broiler breeder roosters supplemented with a slightly lower concentration of Se (0.2 mg/kg of diet) regardless of source, had increased relative testes weights compared with a Se-deficient control. However, increased testicular size does not correspond to increased fertility [28] or greater reproductive hormone levels [29] and any identified relationships between these measures are breed-specific in poultry [30].…”
Section: Discussionmentioning
confidence: 91%